2019
DOI: 10.1093/jn/nxz053
|View full text |Cite
|
Sign up to set email alerts
|

Whey Protein Hydrolysate Increases Amino Acid Uptake, mTORC1 Signaling, and Protein Synthesis in Skeletal Muscle of Healthy Young Men in a Randomized Crossover Trial

Abstract: Background Muscle protein synthesis (MPS) can be stimulated by ingestion of protein sources, such as whey, casein, or soy. Protein supplementation can enhance muscle protein synthesis after exercise and may preserve skeletal muscle mass and function in aging adults. Therefore, identifying protein sources with higher anabolic potency is of high significance. Objective The aim of this study was to determine the anabolic potency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 56 publications
0
34
1
Order By: Relevance
“…However, we have not measured the plasma amino acid levels earlier than 60 min after administration. Moro [22] indicated that the ingestion of WPH induced similar levels of aminoacidemia compared with that of intact whey protein, which is inconsistent with our hypothesis, so further study is necessary to confirm it.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…However, we have not measured the plasma amino acid levels earlier than 60 min after administration. Moro [22] indicated that the ingestion of WPH induced similar levels of aminoacidemia compared with that of intact whey protein, which is inconsistent with our hypothesis, so further study is necessary to confirm it.…”
Section: Discussioncontrasting
confidence: 71%
“…These results indicated it is possible that not only the amino-acid composition but also the difference of molecular form, such as amino acids, peptides or protein, affect skeletal muscle metabolism. Recently, Moro [22] showed that the ingestion of WPH induced a greater transport and accumulation of leucine into muscle, which increased amino acid utilization for protein synthesis compared with the ingestion of intact whey protein. However, it is unclear which is more effective for stimulating MPS, WPH or intact whey protein.…”
Section: Introductionmentioning
confidence: 99%
“…Post-exercise protein ingestion is suggested to increase MPS through the provision of sufficient amino acids, particularly leucine, thus activating the key anabolic signalling mechanism of the mechanistic target of rapamycin (mTOR) (3,4) . Consequently, dietary protein intake is considered an essential component in the optimisation of skeletal muscle adaptations to RT.…”
mentioning
confidence: 99%
“…Therefore, greater relative daily amounts (>2 g•kg −1 •BW•day −1 ), combined with novel isolated intact protein blends as well as protein sources containing high relative proportions of di-and tripeptides (i.e., protein hydrolysates), may be needed to facilitate greater protective effects on muscle during disuse. Indeed, whilst evidence is limited, protein hydrolysates have been observed to be superior to intact proteins, largely due to decreased splanchnic extraction, increased postprandial AA bioavailability and rapid appearance of EAAs, in particular leucine, into circulation [78,[91][92][93]. Moreover, WP hydrolysates have also been observed to augment a greater acute postprandial MPS response compared to intact protein sources in younger and older adults [78,91,93].…”
Section: Supplemental Protein Sourcesmentioning
confidence: 99%
“…Indeed, whilst evidence is limited, protein hydrolysates have been observed to be superior to intact proteins, largely due to decreased splanchnic extraction, increased postprandial AA bioavailability and rapid appearance of EAAs, in particular leucine, into circulation [78,[91][92][93]. Moreover, WP hydrolysates have also been observed to augment a greater acute postprandial MPS response compared to intact protein sources in younger and older adults [78,91,93]. However, ultimately, more chronic investigations are required to assess the longer-term anabolic potential of protein hydrolysates compared with intact (whole) proteins, particularly during periods of disuse and inactivity.…”
Section: Supplemental Protein Sourcesmentioning
confidence: 99%